PENGEMBANGAN MOBILE EDUGAME MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN ARITMATIKA DASAR SISWA SD KELAS 4 DAN 5 - Hardian, Robby (Institut Bisnis dan Teknologi Indonesia, 2019)
The lack of attention to basic arithmetic calculation mastery intuitively causes count stuttering to be found among elementary school students. Counting stuttering is a slow counting condition. To overcome this calculating stutter, one of the instruments that can be used is the Test of Second Mathematics. TOSM is an instrument of Secondary Mathematics in the form of a measuring sheet intended to increase the basic arithmetic calculation speed. In addition to the printed version (written), TOSM has also been created in the mobile application version. However, due to visual limitations, both written TOSM and applications make students gradually become bored and bored. Seeing the popularity of mobile games and the ease of getting them, TOSM will be adopted into mobile edugame with a more attractive visual style. Through the game approach, students will not be aware of doing TOSM. The results of mobile edugame design show that students feel more comfortable and relaxed when working on TOSM in the form of edugame. The adoption of TOSM into edugame provides an entertainment aspect without leaving the initial goal of edugame design, namely as a media to learn basic arithmetic intuitively.